Resource Status and Effect of Long-Term Stock Enhancement of Large Yellow Croaker in China - Yuan, Jigui; Lin, Hungdu; Wu, Lisheng; Zhuang, Xuan; Ma, Junkai; Kang, Bin; Ding, Shaoxiong (Frontiers in Marine Science, 2021)
The large yellow croaker, Larimichthys crocea, was once the most abundant and economically important marine fish in China. Thus far, it has also been the most successful mariculture fish species in China. However, its wild stock severely declined in the 1970s because of overexploitation, and therefore hatchery release has been carried out for stock enhancement since 2000. As a migratory fish, large yellow croaker was divided into three geographical stocks according to ambiguous morphological and biological characteristics in early documents. To investigate the identity of wild large yellow croaker populations and assess the influence of hatchery supplementation on wild populations, a total of 2,785 cultured individuals and 591 wild individuals were collected from 91 hatcheries and six wild populations along the coast of mainland China and analyzed using two mitochondrial genes [cytochrome oxidase I (COI) and cytochrome b (Cyt b)] and one nuclear gene (RyR3). The higher haplotype diversity and moderate nucleotide diversity of wild large yellow croaker indicated that overexploitation, which caused a sharp decrease in biomass, did not lead to a loss of genetic diversity. According to phylogenetic construction and network analysis, the absence of a significant population structure pattern revealed a single panmictic population of wild large yellow croaker with exception of a population collected from the Sansha Bay, which showed high genetic relatedness to the cultured population, suggesting significant genetic effects resulting from stock enhancement. Overall, our study suggests no genetic differentiation in the entire wild population of large yellow croaker, which means that we have great flexibility in mixing and matching farmed and wild populations. However, since the result showed that domestication, the relaxation of purifying selection, increased genetic loads, and maladapted farmed fish will be at a selective disadvantage when cultured juveniles are released in the wild, the effectiveness of stock enhancement and the negative impact of hatchery-wild fish hybridization on the wild population must be carefully evaluated in future.